2017
DOI: 10.1021/acsnano.7b02755
|View full text |Cite
|
Sign up to set email alerts
|

Detection of an Integrin-Binding Mechanoswitch within Fibronectin during Tissue Formation and Fibrosis

Abstract: Fibronectin (Fn) is an extracellular matrix protein that orchestrates complex cell adhesion and signaling through cell surface integrin receptors during tissue development, remodeling, and disease, such as fibrosis. Fn is sensitive to mechanical forces in its tandem type III repeats, resulting in extensive molecular enlongation. As such, it has long been hypothesized that cell- and tissue-derived forces may activate an “integrin switch” within the critical integrin-binding ninth and 10th type III repeats—confe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(77 citation statements)
references
References 38 publications
3
72
0
Order By: Relevance
“…Aside from RGD, there are many integrin‐activating domains into structure of ECM proteins that can enhance stem cell attachment or recruitment . For example, Pro–His–Ser–Arg–Asn is an amino acid sequence, found in fibronectin, whose activation results in the enhancement of signaling responses that initiate stem cell recruitment . Despite these merits, ECM proteins have several major shortcomings that limit their clinical use, such as potential risk of pathogen transmission, unsolicited adverse immune response (against cadaveric or xenogenic proteins), and bioactivity loss owing to conformational changes during conjugation to scaffolds …”
Section: Cell Adhesion Molecules For Surface Modificationmentioning
confidence: 99%
“…Aside from RGD, there are many integrin‐activating domains into structure of ECM proteins that can enhance stem cell attachment or recruitment . For example, Pro–His–Ser–Arg–Asn is an amino acid sequence, found in fibronectin, whose activation results in the enhancement of signaling responses that initiate stem cell recruitment . Despite these merits, ECM proteins have several major shortcomings that limit their clinical use, such as potential risk of pathogen transmission, unsolicited adverse immune response (against cadaveric or xenogenic proteins), and bioactivity loss owing to conformational changes during conjugation to scaffolds …”
Section: Cell Adhesion Molecules For Surface Modificationmentioning
confidence: 99%
“…Indeed, it has been shown that unfolding of 10FnIII creates a critical increase in distance between the Fn10III RGD and Fn9III PSHRN motifs, leading to lowered α5/α3 affinity while αV integrin binding remains unaltered, suggesting a role of cell‐derived forces in autonomically tuning the integrin selectivity of the associated ECM 26. Such “integrin switching” could induce profound implications in numerous biological processes including differentiation, pathological and physiological angiogenesis, and progression of fibrosis 27. Recent efforts in the biomaterials community have attempted to engineer synthetic Fn fragments containing the vital 9FnIII and 10FnIII repeats to better exhibit the mechanosensitive properties of natural Fn and offer tuning of the mechanically induced integrin switch observed in vivo.…”
Section: The Extracellular Matrix: Foundations Of Matrix Mechanics Anmentioning
confidence: 99%
“…High affinity binding of α5β1 integrin to fibronectin requires interactions with both the RGD (Arg-Gly-Asp amino acid sequence) and synergy sites in FN III10 and FN III9, respectively. When the fibril is stretched, the distance between these sites increases which prohibits α5β1 integrin from binding both sites (Figures 2 and 3) [122][123][124], thus altering signaling from α5β1 integrin. Stretching of fibronectin fibrils may also change the 3-D architecture of the ECM because it could alter the binding sites used by fibronectin-binding proteins such as tenascin-C [125], CD44 [126], versican [127], and myocilin [39].…”
Section: Increased Ecm Rigiditymentioning
confidence: 99%